Land-use competition in 1.5°C climate stabilization: is there enough land for all potential needs? - Gurgel, Angelo; Morris, Jennifer; Haigh, Martin; Robertson, Andy D.; van der Ploeg, Robin; Paltsev, Sergey (Frontiers in Environmental Science, 2024)
Achieving a low-carbon future requires a comprehensive approach that combines emission mitigation options from economic activities with the sustainable use of land for numerous needs: food production, energy production, carbon sequestration, nature preservation and broad ecosystem services. Using the MIT Integrated Global System (IGSM) framework we analyze land-use competition in a 1.5°C climate stabilization scenario, in which demand for bioenergy and natural sinks increase along with the need for sustainable farming and food production. We find that to address the numerous trade-offs, effective approaches to nature-based solutions (NBS) and agriculture practices are essential. With proper regulatory policies and radical changes in current practices, global land is sufficient to provide increased consumption of food per capita (without large diet changes) over the century while also utilizing 2.5–3.5 billion hectares (Gha) of land for NBS practices that provide a carbon sink of 3–6 gigatonnes (Gt) of CO2 per year as well as 0.4–0.6 Gha of land for energy production—0.2–0.3 Gha for 50–65 exajoules (EJ) per year of bioenergy and 0.2–0.35 Gha for 300–600 EJ/year of wind and solar power generation. We list the competing uses of land to reflect the trade-offs involved in land use decisions, and note that while there is sufficient land in our scenario, attaining this outcome, capable of delivering a 1.5°C future, requires effective policies and measures at national and global levels that promote efficient land use for food, energy and nature (including carbon sequestration) and ensure long-term commitments by decision makers from governments and industry in order to realize the benefits of climate change mitigation.